Management of patrimonial control and its influence on the high and lower of movable property of the Regional Government Tacna, period 2016. - Chambilla Chambe, Pamela Candy (2019)
The present research work brings together the different aspects of the management of patrimonial control, which influence the additions and cancellations of the movable property of the Regional Government of Tacna, in the 2016 period; Likewise, information on procedures, registration and control of assets, coordination and supervision, norms and directives established by the entity of the Regional Government of Tacna was compiled. The work that was developed is not experimental, descriptive and correlational according to the purpose of the research. The research area is framed in government accounting, because it is an activity aimed at the analysis and evaluation of procedures, registration and removal of movable assets for a good management of patrimonial control, through the evaluation of efficiency, effectiveness, economy of the Entity. The institution subject of study has deficiencies in the control of inventory, this is due to the fact that physical inventories are received without being verified with exhaustive verification, as well as the goods that are obsolete due to technological changes, not having an exact quantity of the assets that are under the administration of the institution, as well as untrained personnel.